Thi kendes for ret - om lemmata og eksempler i juridisk fagleksikografi - Kjær, Anne Lise (HERMES - Journal of Language and Communication in Business, 2017)
This paper will focus on some principles for lexicographical treatment of a type of fixed word combinations, which could be referred to in English as “stereotyped expressions” (in German: “Routineformeln”), more specifically stereotypes commonly and repeated-ly used as stable parts of certain types of legal documents. The question is raised where word combinations of that kind should be placed in a bilingual law dictionary. Should they be placed as entries according to their status as language units? Or shold they be indicated as examples of the use of the words of which they consist? It is argued that neither of the solutions is good. In stead, stereotypes should be cited in articles describing the documents of which they are a stable part.